Analisis Kemampuan Pembuktian Matematis Siswa SMP pada Materi Phytagoras Ditinjau dari Resiliensi dan Gaya Kognitif Siswa - Sirait, Abadihon Fazli; Mujib, Abdul (Media Pendidikan Matematika, 2025)
This study aims to analyze junior high school students’ mathematical proof abilities in Pythagoras’ theorem in terms of resilience and cognitive style. This study uses a qualitative descriptive approach. The research subjects consist of six eighth-grade students selected based on high, moderate, and low categories in the mathematical proof ability test, as well as considering resilience levels (high, moderate, low) and cognitive styles (field independent). Data collection techniques include a mathematical proof ability test, a resilience questionnaire, a GEFT cognitive style test, and interviews. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that students with high resilience and field-independent cognitive styles have good mathematical proof abilities, are able to construct arguments logically and systematically, and are not easily discouraged when solving problems. Students with moderate resilience and field-dependent cognitive styles demonstrated adequate proof abilities but tended to require guidance and were less independent in their thinking. Meanwhile, students with low resilience and field-dependent cognitive styles had low proof abilities, tended to be confused in constructing arguments, and easily gave up when faced with difficulties. This study shows that students’ mathematical proof abilities are influenced by a combination of resilience and cognitive style. Therefore, teachers need to consider both affective and cognitive factors in the mathematics learning process to optimize students’ mathematical thinking abilities, particularly in the aspect of proof